The evaluation of the procedures of excution the national strategy of unti - corruption in Iraq (2014-2010) - محمد, اياد طاهر; كاظم, احمد محمد (Journal of Economics and Administrative Sciences, 2014)
Corruption has become the subject of great interest, and the subject of research and scrutiny in recent years, because of its penetration in all fields of life,  whether these fields are political, economic, social, and administrative. It is one of the biggest challenges and problems that are facing communities. Therefore, this study is focused on the evaluation of measures implementing the national strategy to combat corruption in Iraq.This study was launched, first because of its intellectual dimensions to ensure a conceptual presentation of the strategy and operational management in general with a special focus on the processes of implementation and control strategy which reveals the importance of the research topic.As for the other practical dimension, there were two issues included, in the first one a checklist finder was used to measure the determinants and indicators of success in the implementation of the national strategy for combating corruption. This is done through a field study to assess the measures of implementing the national strategy to combat corruption in some ministries that represent both sectors (i.e. production and service sectors).  These represent the ministries of oil, industry and minerals, health, labor and social affairs. Such work can be approached by conducting interviews with ten members of each ministry who have a role in the implementation of the national strategy to combat corruption, while working, at the same time on the second sector to ensure the display of the percentage of completion for the years (2010,2011, 2012) to address the negative phenomena diagnosed in the national strategy to combat corruption of the surveyed guidelines.